Inventing Ama a transcendental phenomenological study on the lived experiences of Filipino fathers with fatherhood and masculinity - Domingo, Simon C.; Te, Kenneth Mark M.
Literature on fatherhood in both offline and online spaces has long explored how fathers navigate changing gender norms and expectations. However, few studies have focused on how Filipino fathers experience fatherhood across these spaces. This study used transcendental phenomenology to understand the lived experiences of five Filipino fathers and how they make sense of being a father, their masculinity, and their engagements in online platforms. Findings show that fathers navigated tensions between how they were taught to parent and what they are learning through new experiences and connections. Online spaces offered fathers a space to learn, reflect, build connections, and get affirmation. Rather than simply rejecting the past, fathers described a process of negotiation, choosing which practices to continue, question, or adapt in response to their own children’s needs and their own aspirations. This study affirms the need for a more nuanced, non-moralizing understanding of Filipino fathers and calls for further research on how fathers use digital spaces in shaping their journey towards fatherhood. Our study amplifies existing calls for a shift in how we value men’s role in care. To support this shift, we must pay closer attention to how social media shapes the way fathers understand themselves and learn what it means to parent. These platforms are not just tools for communication but spaces where identities are formed, challenges, and refined over time.